Ibrutinib-induced cardiomyopathy - Htay Htay Kyi; Yazan Zayed; Samer Al Hadidi (Journal of Community Hospital Internal Medicine Perspectives, 2019)
The use of ibrutinib for the treatment of chronic lymphocytic leukemia (CLL) and other hematologic malignancies is blooming. Atrial fibrillation is a known side effect of ibrutinib but cardiomyopathy was not reported previously. We present an 88-year-old man with CLL who was admitted to the hospital with new-onset atrial fibrillation and symptomatic systolic congestive heart failure one month after ibrutinib initiation. Although ibrutinib was discontinued, the patient continues to have a low ejection fraction four months after discontinuation. Ischemic heart disease was ruled out with normal cardiac catheterization. This case highlights a possible new side effect of ibrutinib that needs to be monitored while patients receive this medication.